Effect of a multicomponent exercise intervention on brain metabolism: A randomized controlled trial on Alzheimer's pathology (Dementia‐MOVE). Issue 1 (22nd May 2020) - Haeger, Alexa; Costa, Ana S.; Romanzetti, Sandro; Kilders, Axel; Trautwein, Christian; Haberl, Luisa; Beulertz, Michael; Hildebrand, Frank; Schulz, Jörg B.; Reetz, Kathrin
Abstract: Background: Physical activity has shown a positive impact on aging and neurodegeneration and represents a possible treatment option in cognitive decline. However, its underlying mechanisms and influences on brain pathology remain unclear. Dementia‐MOVE (Multi‐Objective Validation of Exercise) is a randomized‐controlled pilot trial, including 50 patients with amnestic cognitive impairment associated with Alzheimer's pathology, aiming to analyze the effect of physical activity and fitness on disease progression. Methods: Dementia‐MOVE is divided into two arms, of either an intervention comprising physical activity, for at least twice a week, combined with a psychoeducational program, or a sole psychoeducational program. Physical activity intervention includes a supervised and unsupervised multimodal concept combining resistance, endurance, coordinative, and aerobic training. The primary outcome is the change of brain metabolism due to physical interventional treatment. Besides metabolic magnetic resonance imaging (MRI) including sodium and phosphorus imaging, resting state functional MRI, T1‐, T2‐weighted and fluid‐attenuated inversion recovery (FLAIR), as well as diffusion‐weighted imaging (DWI) of the brain and whole‐body fat MRI are performed before and after intervention, and will be compared in their sensitivity for the detection of intervention effects. We further assess cognitive performance, neuropsychiatric symptoms, quality of life, fitness, and sleep via questionnaires/interviews and/or fitness trackers, as well as microbiome, under the aspect of Alzheimer's pathology. Discussion: The aim of Dementia‐MOVE is to investigate the effect of a multimodal exercise program on Alzheimer's pathology under different aspects of the disease. In this context, one of the main aims is the comparison of different MRI methods regarding their responsiveness for the detection of alterations induced by physical activity. As an underlying goal, new treatment and diagnostic options, as well as the exploration of fitness effects on brain structure and metabolism within a whole‐body perspective of Alzheimer's disease are envisaged.